Modern approaches to cervical cancer screening (a review) - Pavliuchenko, M. I.; Krut, Yu. Ya.; Siusiuka, V. H.; Deinichenko, O. V.; Павлюченко, Михайло Іванович; Круть, Юрій Якович; Сюсюка, Володимир Григорович; Дейніченко, Олена Валеріївна (Запорізький державний медичний університет, 2023)
The aim – systematization of data from modern scientific sources and own knowledge and experience regarding the problems, advantages and prospects of the development of various methods of diagnosing pathological conditions of the cervix. The relevance of the problem of cervical cancer is beyond doubt, which is confirmed by the annual data of the official statistics and recommendations of WHO, European experts and relevant national recommendations. The analysis and generalization of information from the specialized literature regarding the assessment of problems and prospects for the development of leading methods of cervical screening in order to reduce the number of cervical cancer cases in the world is a priority task of the expert society. Currently, the most recommended approach to cervical screening is to combine HPV testing with cytology but separate testing for HPV is the most promising. Colposcopy remains the only confirmatory method of diagnosing cervical pathology, subject to mandatory cervical biopsy and histopathological examination of the biopsy. Standardization of classifications and terminology in the assessment of cytological, histopathological and colposcopic conclusions will allow to reach an understanding in the issues of optimal management tactics for patients with cervical pathology. Conclusions. Diagnosis of high-risk carcinogenic types of human papillomavirus is the most promising method of cervical screening in the near future. At the same time, at the moment, we consider it appropriate to use the cytology together with HPV testing, at least as a sorting method. Standardization of cytological/histopathological terminology should be done in accordance with the Bethesda 2014 system update. Мета роботи – систематизація відомостей сучасних наукових джерел, власних знань і досвіду щодо проблем, переваг і перспектив розвитку різних методів діагностики патологічних станів шийки матки. Актуальність проблеми раку шийки матки не викликає сумнівів, що підтверджується щорічними даними офіційної статистики та рекомендаціями ВООЗ, європейських експертів і відповідними національними рекомендаціями. Пріоритетне завдання експертного товариства – аналіз та узагальнення відомостей фахової літератури щодо проблем і перспектив розвитку провідних методів цервікального скринінгу для зниження кількості випадків раку шийки матки у світі. Нині під час цервікального скринінгу найчастіше рекомендують поєднання тестування на вірус папіломи людини (ВПЛ) із цитологічним методом дослідження, а найбільш перспективним вважають окреме тестування на ВПЛ. Єдиний вірогідний метод діагностики патології шийки матки – кольпоскопія за умови обов’язкового виконання цервікальної біопсії та патогістологічного дослідження біоптата. Стандартизація класифікацій, термінології під час оцінювання цитологічних, патогістологічних й кольпоскопічних висновків дасть змогу досягти консенсусу щодо оптимальної тактики ведення пацієнток із патологією шийки матки. Висновки. Діагностика висококанцерогенних типів ВПЛ – найбільш перспективний метод цервікального скринінгу в найближчому майбутньому. Втім, доцільним вважають використання цитологічного дослідження разом із тестуванням на ВПЛ, принаймні як метод сортування. Стандартизацію цитологічної / гістопатологічної термінології слід здійснювати відповідно до рекомендацій термінологічної системи Бетесда (2014).
Сучасні підходи до скринінгу раку шийки матки (огляд літератури)
Pavliuchenko M. I. - ORCID ID: 0000-0002-9235-0205; Krut Yu. Ya. - ORCID ID: 0000-0002-0501-6752; Siusiuka V. H. - ORCID ID: 0000-0002-3183-4556; Deinichenko O. V. - ORCID ID: 0000-0002-8932-230X.
Keywords: cervix; precancerous cervical pathology; cervical cancer; human papilloma virus; cervical screening; cytologic method; HPV DNA test; colposcopy; шийка матки; передракова цервікальна патологія; рак шийки матки; вірус папіломи людини; цервікальний скринінг; цитологічний метод; тест ДНК ВПЛ; кольпоскопія